The Effect of Annual Apparent Motion of the Sun on the Early Oscillation of Shubuh Prayer Time (Case Study of Pontianak City) - Asep Saefullah; Diana Ayu Rostikawati; Yuant Tiandho (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2023)
This Study aims to determine the effect of the Sun's annual apparent motion on the oscillations of the Subuh prayer time, especially in the city of Pontianak. The research method used is the literature review or reference method. In the literature review, the things that were done included: looking for the schedule of the dawn prayer in the city of Pontianak over one year, knowing the geographical position of the city of Pontianak, the apparent annual motion of the Sun, and the effect of the annual apparent motion of the Sun on the initial oscillation of the Subuh prayer time. Apart from that, another thing done in the literature review was to look for the influence of the earth-sun distance on the oscillations of the dawn prayer time. The results showed that there were similarities between the oscillations of the annual apparent motion of the Sun and the oscillations of the dawn prayer time in the city of Pontianak. However, there is a time difference with an average of 41 days between the oscillation of the Sun's annual apparent motion and the oscillation of the time of the Subuh prayer. The results of the Study also show that the distance from the Earth to the Sun (aphelion and perihelion) affects the initial oscillation of the dawn prayer time. When the Earth is at the aphelion point, the time for the Subuh prayer falls later than usual. Meanwhile, when the Earth is at perihelion, the time for the dawn prayer falls faster than usual.